Impact of family support on academic performance in the area of social sciences among fifth grade students at san rafael institute in soledad, atlántico. (Original) (Revista científica Olimpia, 2024)
This research examines the impact of family support on the academic performance of fifth-grade students in the Social Studies area at San Rafael Educational Institute in Soledad, Atlántico. The study is based on the idea that active family participation and interest in children’s educational process can have a positive effect on their academic performance. It aims to explore the relationship between family support and educational achievements, with the objective of understanding how the family environment influences student learning.
Keywords: Family Support, Students, Academic Performance, Lack of Support, Social Studies